2020
DOI: 10.2490/prm.20200001
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Japanese Version of a Collaborative Relationship Scale between Clients and Occupational Therapists

Abstract: Objective:The success of a client-centred practice depends on the relationship between the client and therapist and on their ability to make constructive decisions together, particularly in the field of occupational therapy. The aim of this study was to develop a Occupational Therapy Collaborative Relationship Scale (OTCRS) to measure the quality of such interaction. Methods: This work included constructing a draft questionnaire and testing its validity and reliability. A Rasch analysis was applied to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The calculated total score in CRS is classified under three categories based on the estimated values below: poor collaborative relationship group, neutral collaborative relationship group, and good collaborative relationship group (Choji et al, 2020a, 2020b). In this study, the good collaborative relationship group demonstrated significantly higher process skills in AMPS and satisfaction in COPM compared to the poor collaborative relationship group and occupational therapists group, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculated total score in CRS is classified under three categories based on the estimated values below: poor collaborative relationship group, neutral collaborative relationship group, and good collaborative relationship group (Choji et al, 2020a, 2020b). In this study, the good collaborative relationship group demonstrated significantly higher process skills in AMPS and satisfaction in COPM compared to the poor collaborative relationship group and occupational therapists group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The CRS between clients and occupational therapists, developed by Choji et al (2020aChoji et al ( , 2020b, is a standardized assessment simple screening tool to measure the degree of the collaborative relationship between clients and occupational therapists. A collaborative relationship in CRS is defined as the degree of shared authority between clients and occupational therapists when deciding on a client-centered approach from the client's perspective.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation